The ideal city of Al- Farabi. The Birth of Political Philosophy in Islam - Zeraoui, Zidane (2020)
Al Farabi reintroduced the philosophy of Plato and Aristotle into 10 th century Islamic thought, proving that is was the only one capable of explaining the challenge of revealed religions to philosophical thought.  It can be said that al-Farabi's philosophy seems to be the result of a reflection made from Greek philosophy, which is intended to be applied to lived reality. His thought is shown to us as an attempt to introduce a rational consideration of reality in a strictly religious society like the Muslim. Al-Farabi not only managed to introduce Greek philosophy to the Islamic world, but he integrated political thought into Muslim society. Try to achieve a synthesis between prophecy and philosophical reflection.